2023
DOI: 10.3389/fped.2023.1197713
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the treatment provided for children with unilateral hearing loss

Roshni Patel,
Derek J. Hoare,
Karen R. Willis
et al.

Abstract: BackgroundChildren with permanent unilateral hearing loss (UHL) are an understudied population, with limited data to inform the guidelines on clinical management. There is a funding gap in healthcare provision for the children with UHL in the United Kingdom, where genetic screening, support services, and devices are not consistently provided or fully funded in all areas. They are a disparate population with regard to aetiology and their degree of hearing loss, and hence their device choice and use. Despite hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…As a matter of fact, parents often perceive professionals’ hesitation and lack of conviction about the potential benefits of hearing aids in children with USNHL, as well as professionals’ tendency to minimize the importance of milder HL [ 38 ]. However, only one of our patients did not use a hearing aid due to lack of benefit after an adequate trial period, confirming that most children with UNSHL who have tried a hearing device continue to use it [ 9 , 33 ]. The subjective benefit of wearing a hearing aid was also indirectly proven by the high mean daily hearing aid use, with all but one of our patients using the device for at least 7 h per day.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…As a matter of fact, parents often perceive professionals’ hesitation and lack of conviction about the potential benefits of hearing aids in children with USNHL, as well as professionals’ tendency to minimize the importance of milder HL [ 38 ]. However, only one of our patients did not use a hearing aid due to lack of benefit after an adequate trial period, confirming that most children with UNSHL who have tried a hearing device continue to use it [ 9 , 33 ]. The subjective benefit of wearing a hearing aid was also indirectly proven by the high mean daily hearing aid use, with all but one of our patients using the device for at least 7 h per day.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, one in five children was diagnosed with unilateral vestibular hypofunction, reinforcing the need for routine vestibular and balance assessment in all pediatric patients with USNHL, as already suggested by previous studies [ 31 , 32 ]. Although several studies have demonstrated the negative consequences and long-term implications of uncorrected USNHL [ 9 , 13 , 14 , 15 , 16 ], less than half of our patients used a hearing device. The high percentage of non-users of hearing devices was largely attributed not only to aesthetic concerns due to social stigma, but also to parents’ lack of knowledge since this solution had never been proposed before by professionals.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations